2014
DOI: 10.3389/fimmu.2014.00611
|View full text |Cite
|
Sign up to set email alerts
|

The Role of microRNAs in Bovine Infection and Immunity

Abstract: MicroRNAs (miRNAs) are a class of small, non-coding RNAs that are recognized as critical regulators of immune gene expression during infection. Many immunologically significant human miRNAs have been found to be conserved in agriculturally important species, including cattle. Discovering how bovine miRNAs mediate the immune defense during infection is critical to understanding the etiology of the most prevalent bovine diseases. Here, we review current knowledge of miRNAs in the bovine genome, and discuss the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 70 publications
2
43
0
4
Order By: Relevance
“…Although limited research has been conducted, microRNAs have been implicated in the immune response associated with BRD infection in cattle (Lawless et al . ). For example, four microRNAs ( bta‐miR‐24‐3p, bta‐miR‐92a, bta‐423‐5p and bta‐let‐7b ) were differentially expressed in beef cattle that were seropositive for M .…”
Section: Resultsmentioning
confidence: 97%
“…Although limited research has been conducted, microRNAs have been implicated in the immune response associated with BRD infection in cattle (Lawless et al . ). For example, four microRNAs ( bta‐miR‐24‐3p, bta‐miR‐92a, bta‐423‐5p and bta‐let‐7b ) were differentially expressed in beef cattle that were seropositive for M .…”
Section: Resultsmentioning
confidence: 97%
“…More identifications of the bovine miRNA expression atlas in different tissues and cells are necessary to further fill in the gap (Lawless et al . ,). These newly identified miRNAs could significantly expand the bovine miRNA spectrum and refine their annotations.…”
Section: Resultsmentioning
confidence: 99%
“…Using next‐generation sequencing and RT‐PCR approaches, several studies have identified differentially expressed bovine miRNAs, target genes, KEGG pathways and related regulatory networks and pointed out their roles in regulating host response to S. aureus or Escherichia coli , in vivo and in vitro , at early stages of infection (Lawless et al . , ,; den Breems et al . ; Jin et al .…”
Section: Introductionmentioning
confidence: 99%
“…MiRNAs have been shown to play roles in bovine infection and immunity in a wide range of tissues [54,[106][107][108][109][110][111][112][113]. For mammary gland, Naeem et al [114] studied the expression of 14 miRNAs (miR-10a, miR-15b, miR-16a, miR-17, miR-21, miR-31, miR-145, miR-146a, miR146b, miR-155, miR-181a, miR-205, miR-221 and miR-223) in MG tissue challenged with Streptococcus uberis and identified three downregulated miRNAs (miR-181a, miR-16 and miR-31) and one upregulated miRNA (miR-223) in infected versus healthy tissue.…”
Section: Microrna Functions In Mammary Gland Healthmentioning
confidence: 99%